2018
DOI: 10.1016/j.theriogenology.2017.12.012
|View full text |Cite
|
Sign up to set email alerts
|

Effect of storage temperature, nitrogen gassing and sperm concentration on the in vitro semen quality and in vivo fertility of liquid bull semen stored in INRA96

Abstract: The aim of this study was to assess the effect of storage temperature, nitrogen (N) gassing and sperm concentration on in vitro characteristics and calving rate (CR) following artificial insemination (AI) of liquid bull semen stored in INRA96. In Experiment 1 the effect of liquid bull semen diluted in either N bubbled or non-bubbled INRA96 at a concentration of 5 × 10 sperm per 0.25 mL insemination dose and stored at 5 or 15 °C was assessed subjectively for total and progressive motility on Days 0, 1, 2, 3 and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 29 publications
0
9
0
Order By: Relevance
“…With regard to sperm concentration, the beneficial effect of storing goat sperm doses at low sperm concentration on sperm motility and kinetics was not evident, as observed by other research groups [ 4 , 9 , 11 ]. Different results of sperm motility were obtained in the different experiments of the present study.…”
Section: Discussionmentioning
confidence: 66%
See 2 more Smart Citations
“…With regard to sperm concentration, the beneficial effect of storing goat sperm doses at low sperm concentration on sperm motility and kinetics was not evident, as observed by other research groups [ 4 , 9 , 11 ]. Different results of sperm motility were obtained in the different experiments of the present study.…”
Section: Discussionmentioning
confidence: 66%
“…In contrast, Murphy et al [ 4 ] found that bovine spermatozoa stored at lower concentrations showed greater viability and reduced glucose consumption. However, no effect of sperm concentration on sperm PM and hMMP was found [ 4 , 11 ]. This disagreement could be attributed to the use of different species and methodology, and that the fact that they did not use any CASA system for sperm motility assessment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although extenders preserve sperm motility even up to three days after collection [23,43], insemination with fresh semen kept longer than 48 h is associated with lower conception rates than insemination with previously frozen semen [44]. The ability of sperm to migrate through artificial mucus in vitro is weakened after 48 h [45], and the causes may relate to motility, time window, extender, viability, the individual bull, and other factors.…”
Section: Discussionmentioning
confidence: 99%
“…Optimum fertility can be achieved with a much lower sperm number when fresh (liquid) rather than frozen-thawed semen is used (2 to 5 million v. 15 to 20 million sperm, respectively; Murphy et al, 2017), maximising the utilisation of genetically superior sires. The higher sperm numbers in cryopreserved semen compensate for the damage during the freeze-thaw process compared with fresh semen and, on average, the same level of fertility is achieved with both types of semen (Murphy et al, 2015).…”
Section: Do Artificial Insemination Bulls Rank the Same When Used Undmentioning
confidence: 99%